2020
DOI: 10.1017/wsc.2020.67
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Palmer amaranth (Amaranthus palmeri) to herbicides in accessions collected from the North Carolina Coastal Plain

Abstract: Palmer amaranth (Amaranthus palmeri S. Watson) populations resistant to acetolactate synthase-inhibiting (ALS) herbicides and glyphosate are fairly common throughout the state of North Carolina (NC). This has led farm managers to rely more heavily on herbicides with other sites of action (SOA) for A. palmeri control, especially protoporphyrinogen oxidase- and glutamine synthetase inhibitors. In the fall of 2016, seeds from A. palmeri populations were collected from the NC Coastal Plain, the state’s most promin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 25 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…The current herbicide program for Palmer amaranth control in sweetpotato is heavily reliant on PRE herbicides including flumioxazin or fomesafen preplant, and S-metolachlor posttransplant (KM Jennings, personal communication; SC Smith and LD Moore, unpublished data). The evolution of protoporphyrinogen oxidase (PPO)-inhibiting herbicide-resistant Palmer amaranth biotypes have been reported in the United States (Heap 2020), including North Carolina (Mahoney et al 2020), which produces more sweetpotato than any other state (USDA-NASS 2020). Therefore, an urgent need exists for alternatives to flumioxazin and fomesafen to control Palmer amaranth in sweetpotato.…”
Section: Introductionmentioning
confidence: 99%
“…The current herbicide program for Palmer amaranth control in sweetpotato is heavily reliant on PRE herbicides including flumioxazin or fomesafen preplant, and S-metolachlor posttransplant (KM Jennings, personal communication; SC Smith and LD Moore, unpublished data). The evolution of protoporphyrinogen oxidase (PPO)-inhibiting herbicide-resistant Palmer amaranth biotypes have been reported in the United States (Heap 2020), including North Carolina (Mahoney et al 2020), which produces more sweetpotato than any other state (USDA-NASS 2020). Therefore, an urgent need exists for alternatives to flumioxazin and fomesafen to control Palmer amaranth in sweetpotato.…”
Section: Introductionmentioning
confidence: 99%
“…acre -1 ) controlled all accessions. More recently, Mahoney et al (2020) surveyed 110 accessions collected from the North Carolina Coastal Plain in 2016 and reported that at least 96% of the accessions survived glyphosate (0.75 lb acre -1 ) and thifensulfuron-methyl (0.016 lb acre -1 ). Fomesafen (0.25 lb acre -1 ) and mesotrione (0.1 lb a.i.…”
mentioning
confidence: 99%
“…acre -1 ) controlled these accessions 98 and 90%, respectively, while no accessions survived glufosinate (0.4 lb acre -1 ). Since Mahoney et al (2020) collected the Palmer amaranth accessions in 2016, evolved resistance to 2,4-D, dicamba, and S-metolachlor has been reported in the United States (Heap, 2021). Although Palmer amaranth with resistance to atrazine was first confirmed in the United States in 1995, resistance to this herbicide has not been reported © 2021 The Authors.…”
mentioning
confidence: 99%
See 2 more Smart Citations